2009
DOI: 10.1143/jjap.48.115505
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Excimer Laser Annealing on InGaZnO4Thin-Film Transistors Having Different Active-Layer Thicknesses Compared with Those on Polycrystalline Silicon

Abstract: Excimer laser annealing (ELA), which can raise the temperature of InGaZnO 4 (IGZO) films for a desired very short time, is effective for obtaining good transfer characteristics in IGZO thin-film transistors (TFTs) on plastic substrates. In this study, we investigate the dependence of the effects of ELA on IGZO-TFTs in comparison with that of its effects on low-temperature polycrystalline silicon (LTPS) for various film thicknesses. We show that the optimum laser energy density with respect to TFT performance d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…Minami et al reported that Si-doped ZnO shows a high conductivity. 23 Although Nakata et al suggested that the reason of the carrier density increasing in a-IGZO film by irradiation of high energy in ELA process would come from the increasing of the amount of oxygen deficiency, 11 we obtained lower O def by the irradiation of high laser energy of 97.7 mJ/cm 2 compared with the O def of no-ELA process, as shown in Fig. 3.…”
mentioning
confidence: 49%
See 1 more Smart Citation
“…Minami et al reported that Si-doped ZnO shows a high conductivity. 23 Although Nakata et al suggested that the reason of the carrier density increasing in a-IGZO film by irradiation of high energy in ELA process would come from the increasing of the amount of oxygen deficiency, 11 we obtained lower O def by the irradiation of high laser energy of 97.7 mJ/cm 2 compared with the O def of no-ELA process, as shown in Fig. 3.…”
mentioning
confidence: 49%
“…10 This technique has also been utilized for oxide-semiconductor materials. Nakata et al reported the fabrication of a-IGZO TFTs by ELA process, which acted as a postannealing process, and the improvement of the TFTs characteristics by ELA, 11 suggesting that the ELA process is also a promising technique for improving the characteristics of oxide-semiconductor devices. In this study, we focused on an IZO TFT with a higher field-effect mobility than an a-IGZO TFT.…”
mentioning
confidence: 99%
“…In the legend S means “solution processed” (data compiled from refs. 66, 78–276 only dealing with GIZO TFTs, the ones corresponding to solution process are in Tables 2a, b and c.…”
Section: Recent Progress Of N‐type Oxide Tftsmentioning
confidence: 99%
“…Amongst the different metal‐oxide semiconductors, IGZO has been well studied in the context of postdeposition laser treatment. A series of pioneering studies on sputtered IGZO TFTs and the impact of XeCl excimer laser irradiation (308 nm) were reported by Nakata et al In addition to their studies on laser annealed IGZO TFTs on glass and polymer substrates, their work also included an investigation of the temperature gradient during laser annealing. Their calculations showed that LA (fluence 150 mJ cm −2 ) of the 20 nm thick IGZO film induced a dramatic 1500 °C temperature increase in the semiconductor but only 12 and 6 °C change for the polymer and glass substrates, respectively.…”
Section: Laser Annealingmentioning
confidence: 99%